PELATIHAN KEWIRAUSAHAAN “MENUMBUHKAN JIWA PEMUDA YANG BERKARAKTER ENTREPRENEUR” DI SMA NEGERI 1 HULU KUANTAN KABUPATEN KUANTAN SINGINGI - Dedi Dermawan; Satriadi Satriadi; Zayyinul Hayati Zen; St. Nova Meirizha; Faradila Ananda Yul (Jurnal Pengabdian UntukMu NegeRI, 2018)
Entrepreneurial ability is the basic capital for someone who wants to move in a particular business field. There are some people who believe that entrepreneurial ability isa gift that is born from birth, this opinion is wrong. Entrepreneurial ability is not due to talent factors, but also arises and feels through entrepreneurial experiences and training. The importance of understanding the world is important to the people in Kuantan Singingidistrict, in order to empower human resources to be able to manage the huge potential of natural resources. That can be done, among others, by providing training to students, this isdone because the introduction of entrepreneurship must be learned and instilled from ayoung age. In this regard, Industrial Engineering study program at the University ofMuhammadiyah Riau opens opportunities for students who want to develop and developtheir entrepreneurial spirit to get Knowledge and plan a business. This was applied tocommunity service with the Entrepreneurship Training "Growing the Soul of Youth with Entrepreneurial Characteristics" in Hulu Kuantan 1 Public High School, Kuantan Singingi District.